Birds of Nicaragua : A Field Guide - Chavarría-Duriaux, Liliana; Chavarría-Duriaux, Liliana; Hille, David C. (1981- ...) (Book collections on Project MUSE., 2018)
La 4e de couverture indique: "Field guide for identifying birds in the field in Nicaragua. Includes body measurements, country-specific range maps, field marks for identification, key comparisons with similar species, vocalization descriptions, scientific names, and English and Spanish common names. Includes alphabetical quick-find index on the inside back cover."